PENGARUH MANAJEMEN PENGETAHUAN TERHADAP BUDAYA ORGANISASI DAN KEPUASAN KERJA YANG DI MEDIASI OLEH KETERLIBATAN PEGAWAI PADA DINAS PPKBP3A KABUPATEN KONAWE KEPULAUAN - Andri Yayu; Sudirman Zaid; Yusuf; Dzulfikri Azis Muthalib (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the influence of knowledge management on organizational culture, job satisfaction, and employee engagement, as well as the influence of employee engagement on organizational culture and job satisfaction, including its role as a mediating variable at the PPKBP3A Office in Konawe Islands Regency. The study used a quantitative approach with a survey method through questionnaires distributed to employees and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The results showed that knowledge management did not have a positive and significant effect on organizational culture, but had a positive and significant effect on job satisfaction and employee engagement. Furthermore, employee engagement had a positive and significant effect on organizational culture and job satisfaction, and was proven to mediate the influence of knowledge management on organizational culture and job satisfaction. These findings indicate that employee engagement is a crucial factor in strengthening the influence of knowledge management on organizational culture formation and increasing job satisfaction.